Tactical training of elite athletes in Olympic combat sports: practice and experience - Zadorozhna, O.; Briskin, Y.; Pityn, M.; Perederiy, A.; Neroda, N. (Trends in Sport Sciences, 2020)
The work studied specifics of tactical training in Olympic combat sports. According to the current researches, technical and tactical training is the basis of athletes` training, but in most papers and official documents, tactical training is not substantiated. Aim of Study. This study aimed to analyze the practical experience of tactical training performed by elite athletes in Olympic combat sports. Material and Methods. We have recruited 40 coaches. Their average experience was almost 15 years. Experts had to rank the components of tactical training such as directions, means, and methods of tactical training, control of tactical preparedness, components of tactical knowledge. Results. In some questions expert`s opinions were similar, but in other questions, they were different inside groups and between them. Average and strong concordance (p < 0.05) was found in such groups of experts: fencing - about directions of tactical training (0.56); verbal, visual and practical methods (0.53; 0.63; 0.62 respectively); means and methods of control (0.53); wrestling - about directions and practical methods(0.74 and 0.59 respectively); boxing - only about practical methods (0.56); taekwondo - about directions (0.58); verbal, visual and practical methods (0.55; 0.64; 0.73 respectively); means and methods of control (0.64); karate - about verbal, visual and practical methods (0.62; 0.64; 0.70 respectively); means and methods of control (0.72); information blocks "Basics of Tactics in Sports" (0.55) and "Competition performance" (0.61). In judo, concordance was weak in all questions (0.41-0.45). Conclusions.The general algorithm of tactical training of elite athletes consists of six steps and is aimed to prepare for the main competition of the year (the Olympic Games or World Championship). The tasks are to choose an effective strategy; to develop the most effective tactical actions against the main rivals; to train to make correct decisions during the bout; to learn how to predict the opponent`s actions